Reprint. From: portfolio "60. Jahrestag der Novemberrevolution/60. Jahrestag der Gründung der KPD" - Jahnke, ..., (1958)
Reprint. From: portfolio "60. Jahrestag der Novemberrevolution/60. Jahrestag der Gründung der KPD".